Ustadzah Halimah Alaydrus's Preaching Rhetoric Through YouTube Social Media (Analysis of the "Household" Theme on Ustadzah Halimah Alaydrus's Channel) - Lisa Imroatul Jannah (Quality : Journal Of Education, Arabic And Islamic Studies, 2025)
Preaching is a noble activity in which a da'i broadcasts the teachings of Islam to mad'u. Therefore, before preaching the da'i should know the strategies to support the success of his da'wah, such as the Science of Rhetoric. Rhetoric is the art or science of the style of language used in conveying a message when speaking in public such as da'wah, speech and others. Ustadzah Halimah Alaydrus is a preacher whose da'wah is currently being heard by Muslimah congregations both offline and online. Ustadzah Halimah when preaching on social media apart from never meeting the congregation directly, she also never showed her face to the congregation online. However, this does not stop the congregation from listening to the da'wah he conveys. This is what makes the writer interested in making it a subject in research. From the background above, the question arises, how is Ustadzah Halimah Alaydrus rhetoric applied? And in this research the author focuses on using the theory of five rhetorical methods written by Zainul Ma'arif in his book Retorika Metode Komunikasi Publik which consists of finding da'wah material (inventio), arranging da'wah texts (dispositio), style of language (elucitio), remembering da'wah material (memoria), and the delivery of da'wah (pronontio). In this research, the author uses a library research method or approach, and based on the results of the rhetorical analysis of Ustadzah Halimah Alaydrus da'wah, the author obtained five rhetorical methods that were applied by Ustadzah Halimah when preaching on youtube social media. The five rhetorical methods of da'wah that she conveys are quite complete, packaged in an attractive manner so that the da'wah material is conveyed correctly, although there are still many shortcomings and these will be described in this research.